Composição lipídica de peixes de extrativismo e de cativeiro - Petenuci, Maria Eugênia (2016)
The beneficial effect of fish consumption is related to polyunsaturated fatty acids content, such as α-linolenic acid (ALA), eicosapentaenoic (EPA) and docosahexaenoic (DHA). These fatty acids have positive effects on human health, as indicated by several studies, reducing the risk factors of cardiovascular disease, hypertension and inflammatory diseases, among others. However, the fish fatty acids composition is not constant, varying depending on several factors such as seasonality, diet, life cycle, temperature and external factors. Therefore, the knowledge of fish fatty acids composition, especially the essential fatty acids, will provide a better understanding of the nutritional value of fish and allow diets and industrial processes be properly measured. This study aimed to evaluating the fatty acid composition of fish species in the Amazon Basin (native) and fish-farmed fish (Nile tilapia), quantify the essential fatty acids, evaluating the nutritional profile of lipid fraction and methods of fatty acids quantification. Moreover, evaluate the effect of seasonality and diet on fatty acids composition. Fish samples in the Amazon basin were collected respectively in Roraima-RR (02 ° 49 '12 "S, 60 ° 40' 23" W) and Mato Grosso - MT (13 ° 1 '59 "S, 55 ° 56 '38 "W). The first collection consisted of the following species: Colossoma macropomum, Leporinus friderici, Prochilodus nigricans, Brachyplatystoma flavicans and Brachyplatystoma filamentosum. The second collection of native fish consisted of the following species: Brycon cephalus and Brycon microlepis. The fish-farmed fish (Oreochromis niloticus) were provided by the Experimental Station UEM/CODAPAR and were collected in Floriano district of Maringá-PR. All samples were handled in accordance with animal welfare standards. The samples were processed; the filet was obtained, crushed, homogenized and stored in plastic bags at -18°C. Subsequently, the samples were characterized by moisture content and total lipids. The species B. cephalus and B. microlepis have their centesimal composition determined, and total lipids were used for further separation of lipid classes. The methyl esters were prepared and separated into gas chromatograph equipped with flame ionization detector and capillary column of cyanopropyl (100 m x i.d. 00:25, 12:25 micrometres CP-7420). Quantification of fatty acids was performed using the internal standard method with methyl tricosonoate (23:0). Samples of the second test had their fatty acid composition determined by four different methods: the area normalization, internal standard, alternative theoretical method and experimental alternative method. Data were statistically analyzed by analysis of variance (ANOVA), and the differences between means were determined by Tukey test at 5% probability. In some cases, it was applied Principal Component Analysis methodology (PCA), in order to assess the variables with the greatest impact on the results. For Nile tilapia were prepared three diets supplemented with 2.1% soybean oil (control), canola oil (TII) and chia oil (TIII). The fish were fed three different times: zero time, 15 days and 30 days. The five fish species from Branco River, Roraima, showed variation in lipid profile according to seasonality of periods of drought and flood. B. flavicans showed the greatest variation between the periods (6.75-15.43%), while C. macropomum showed no significant difference (p>0.05). The species L. friderici, B. flavicans and B. filamentosum showed reduction in total lipids during flood period, which could be related to the species characteristics, to L. friderici the flood period is characterized by reproduction period, i.e, there is a large expenditure of energy for the formation of gametes needed at this time. For the species B. filamentosum and B. flavicans with carnivorous characteristics, at flood period higher energy expenditure is required in search of food in the flooded areas, covering therefore greater distances. A variation was also observed in fatty acids composition according to seasonal periods. In the drought period the content of saturated fatty acids (SFA) was higher and in the flood period, monounsaturated fatty acids (MUFA) and polyunsaturated (PUFA) showed the highest values. This increase in PUFA in the flood period is mainly related to the feeding of species, due to the abundance and diversity of food in the flooded areas, such as flowers, fruits, insects and seeds. These foods have high contents of precursors such as linoleic acid (LA, 18:2n6) and α-linolenic acid (ALA, 18:3n3), which through dessaturation and elongation processes synthetize the long chain PUFA, arachidonic (ARA, 20:4n-6), EPA (20:5n-3) and DHA (22:6n-3). The species L. friderici showed the highest content of ALA (14.86 mg g-1), while C. macropomum showed the highest content of DHA. P. nigricans had the lowest content of ARA in both periods, while B. flavicans showed the highest ARA values in both periods, with 18.77 mg g-1 in drought period and 10.22 mg g-1 in flood period. The indices of atherogenicity and thrombogenicity showed significant differences (p <0.05) between the seasonal periods for all species evaluated. The ratio HH (hypercholesterolemic/hypocholesterolemic) was higher in the flood period, with a significant difference (p <0.05) between species and seasonal periods. The values ranged from 1.91 (B. flavicans) to 2.66 (C. macropomum). Brycon species showed similar proximate composition to other studies, however they were significant different (p <0.05) from each other. The fatty acids composition was determined by four different methods: area normalization (MAN), internal standard (MIS), theoretical alternative method (MAT) and experimental alternative method (MAE). A significant difference (p<0.05) was observed between the methods employed and the species. MAN supplied information in percentage of relative area, which hinders their use in formulating diets, requiring accurate information. MIS, MAT and MAE provided the fatty acids composition of B. cephalus and B. microlepis in mass. B. microlepis had the highest content of ALA, while the sum of the fatty acids EPA and DHA was 104.37 mg 100g-1 and 117.89 mg 100g-1 to B. cephalus and B. microlepis, respectively. The diets formulated for the Nile tilapia feed showed similar composition, with no significant difference (p>0.05). Furthermore, the diets fatty acids composition showed that the treatment with chia oil (TIII) and canola oil (TII) have higher content of polyunsaturated fatty acids, in particular the n-3 series, than control treatment with soybean oil. The results showed a significant difference (p<0.05) between the treatments employed, and TII and TIII treatments incorporated higher amounts of PUFA and of long chain polyunsaturated fatty acids (LC-PUFA) than control (TI). These treatments provided respectively 33.16 mg g-1 and 58.96 mg g-1 of LNA. Compared to TI, this amount was higher around 30% for TII and 131% for TIII. At the end of 30 days of treatment, there was an increase of 97% in DHA content in tilapia fed with TIII and 91% in fed with TII. This increase is related to fish ability to synthesize long-chain fatty acids from ALA and LA precursors. PCA applied to the parameters: n-6, n-3, ALA, LA, DHA, ARA and the ratio n-6/n-3 showed that two main components explained 92.07% of data variance, promoting separation of treatments. The results showed that the fatty acids content of n-3 and n-6 influenced the separation of groups and consequently the results obtained. Fish from the Amazon Basin (state of Roraima) have their lipid profile, the fatty acids composition and the nutritional profile of lipid fraction affected by seasonality. However, in both periods species showed excellent content of polyunsaturated fatty acids, particularly the essential and health-benefiting fatty acids. Regarding the method for fatty acids quantification of the two Brycon species from the Central Amazon basin (Mato Grosso state), it was observed that the method with higher accuracy in the results was the internal standard method. Although alternative methods provided results in mass, generally they showed overestimated values, which can lead to erroneous information on diets and sizing process and product formulations. The Nile tilapia submitted to different treatments have their fatty acids composition influenced by the treatment received, therefore treatment with chia oil and canola promoted a greater incorporation of fatty acids of the n-3 series, beneficial to human health.